Strategies of word identification: Phonetics from a New Perspective - Barbara J Fox (1996)
The book is divided into seven chapters. Chapter 1 explains a strategy approach to word identification. Chapter 2 describes how emergent readers and writers develop insights into the form and function of written language and into the words, rhymes, and sound of spoken language. Chapter 3 explores four early word identification strategies. chapter 4 describes two strategies: the analogy strategy and the crosschecking strategy. Chapter 5 explains the letter-sound strategy. Chapter 6 describes the chunk strategy. Chapter 7 explains why some learners need extra help and what you can do to help them